Development of controller software system for CAM manufacturing machine - Mogan, Arasappan (2009)
This thesis is about developing controller software system for cam manufacturing machine by using cam parametric equations as a guide. Cam development is based on the cam shapes, follower types, and also the applications. Performance of a cam profile affects the speed of the system and the higher the speed, the system will experience more vibrations which lead to defectiveness of the system. These vibrations also may occur due to sudden acceleration of the cam surface once they were produced with unsmooth surface. In order to produce highly performance of cam, it has to have a smoothest surface of contact with the follower. The objective of this project is divided to two most important criteria which to derive a parametric equation system for both x and y axis from a relative cam parametric equation of motion and also to simulate a cam profile using parametric equation of motion by programming methods. The results of this project are from both graphical and programming methods and the results of each cam motions will be discussed. Finally, for conclusion and recommendation of this project, we will conclude the results and whether the objective of this project is achieved and we will also recommend little recommendation on how to improve the results obtain for further research to come.